Гіперлептинемія та стан інсулінової резистентності у хворих на цукровий діабет 2-го типу з ожирінням - Суслик, Г. І. (Clinical Endocrinology and Endocrine Surgery, 2012)
The aim of the study was to explore the features of the concentration of leptin, insulin resistance parameters in patients with type 2 diabetes mellitus and obesity. A total of 77 obese patients with type 2 diabetes mellitus and 32 patients with type 2 diabetes mellitus and physiological BMI, 20 patients with abdominal obesity and the physiological glucoseolerance test were observed. The test groups were same by age and disease duration. The blood concentration of immunoreactive insulin, leptin in patients and insulin resistance indexes was determined. The distinct increase in blood circulating insulin in patients with type 2 diabetes mellitus and obesity was found. In patients with type 2 diabetes mellitus and severe obesity it was detected hiperleptinemia, which is in direct proportion with increasing BMI. There is a strong correlation between the concentration of leptin and insulin, leptin and HOMA-IR.